Modelling shear wave propagation in soft tissue surrogates using a finite element‐ and finite difference method. Issue 1 (25th January 2021) - Ohlsen, Jakob; Neidhardt, Maximilian; Schlaefer, Alexander; Hoffmann, Norbert
Abstract: Shear Wave Elasticity Imaging (SWEI) has become a popular medical imaging technique [1] in which soft tissue is excited by the acoustic radiation forces of a focused ultrasonic beam. Tissue stiffness can then be derived from measurements of shear wave propagation speeds [2]. The main objective of this work is a comparison of a finite element (FEM) and a finite difference method (FDM) in terms of their computational efficiency when modeling shear wave propagation in tissue phantoms. Moreover, the propagation of shear waves is examined in experiments with ballistic gelatin to assess the simulation results. In comparison to the FEM the investigated FDM proves to be significantly more performant for this computing task.